Analisis Quasi Eksperimental Penerapan Model Problem Based Learning (PBL) terhadap Peningkatan Hasil Belajar Ekonomi di SMA Negeri 6 Gorontalo Utara - Dwi Rantikawati Potutu; Radia Hafid; Abdulrahim Maruwae; Frahmawati Bumulo; Maya Novrita Dama (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to determine, the effect of applying the Problem-Based Learning (PBL) model on students’ learning outcomes for Economics subjects in class XI of SMA Negeri 6 Gorontalo Utara. This quantitative research uses a Quasi-Experimental Design research (Pseudo experiment), with a sample size of 30 students. The results showed that there is an effect of applying the Problem-Based Learning (PBL) model, proven to significantly improve the learning outcomes of grade XI students in economic subjects at SMA Negeri Gorontalo Utara, as shown by the Sig. (2-tailed) of 0.000, which is smaller than the significance level of 0.05. The Problem Based Learning (PBL) model allows students to be more active, critical, and independent in understanding concepts by linking theory with real problems.